Numerical Study on Mixed Convection Flow and Energy Transfer in an Inclined Channel Cavity: Effect of Baffle Size - Sivanandam Sivasankaran; Kandasamy Janagi (Mathematical and Computational Applications, 2022)
The objective of the current numerical study is to explore the combined natural and forced convection and energy transport in a channel with an open cavity. An adiabatic baffle of finite length is attached to the top wall. The sinusoidal heating is implemented on the lower horizontal wall of the open cavity. The other areas of the channel cavity are treated as adiabatic. The governing equations are solved by the control volume technique for various values of relevant factors. The drag force, bulk temperature and average Nusselt number are computed. It is recognised that recirculating eddies beside the baffle become weak or disappear upon increasing the inclination angle of the channel/cavity. The average thermal energy transportation reduces steadily until the Ri = 1 and then it rises for all inclination angles and lengths of the baffle.